The security of infants - Flint, Betty M. (Betty Margaret), 1920- (University of Toronto Press, 1959)
This book contains a great deal of information about the personality of young babies. But its greatest fascination lies not in the information it is able to supply but in the many unanswered questions it raises. The author is convinced that each baby manifests his particular personality qualities very early in life, and the way that these are received by the environment into which he has been thrust will largely determine how he will stand up to the stresses of his future life. The development of a mental health assessment form as a yardstick by which a large variety of babies can be evaluated should help unfold some of the teasing obscurities of personality as they are revealed in infancy. If personality is a constant from early life to adulthood, such an instrument, revealing basic qualities in infancy, should lead therefore to greater understanding through school age and to adulthood and help reveal the effect of environmental experiences on a growing child. The thesis of the book is that mental health in infancy is derived from a close dependent relationship with a mother-figure who gives a child an opportunity to form a dependent trust in her care and affection. From this relationship is derived the desire to become effortful, outgoing and independent in one's world, which leads eventually to trust in oneself as a person of uniqueness and worth. The book should have greatest appeal to child care workers, psychiatrists and pediatricians. Research centres for child development should be interested in the experimental aspect of the work.